2016
DOI: 10.4067/s0034-98872016000300005
|View full text |Cite
|
Sign up to set email alerts
|

Asociación de la resistina con variables de dimensión y composición corporal en eutróficos y obesos

Abstract: (Rev Med Chile 2016; 144: 307-316)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…The evidence regarding the role of resistin in obesity and MS in children has been shown to be conflicting. Some authors have reported positive correlations between resistin and markers of obesity and the MS in children [17–19], while others have not [20, 21]. Adipsin, another adipokine, has been attributed proadipogenic properties by triggering triglyceride synthesis and adipocyte differentiation [22].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence regarding the role of resistin in obesity and MS in children has been shown to be conflicting. Some authors have reported positive correlations between resistin and markers of obesity and the MS in children [17–19], while others have not [20, 21]. Adipsin, another adipokine, has been attributed proadipogenic properties by triggering triglyceride synthesis and adipocyte differentiation [22].…”
Section: Introductionmentioning
confidence: 99%
“…Para el caso de los obesos, los terciles fueron 4.148,6 ± 830,2; 4.639,6 ± 1.064,7; y, 4.947,2 ± 1.132,3. Con relación a nuestro estudio, se evidenciaron valores ligeramente mayores a los reportados en otros estudios (25,26) .…”
Section: Discussionunclassified